COLLABORATIVE GOVERNANCE IN THE PREVENTION HIV AND AIDS iN YOGYAKARTA CITY - Erni Saharuddin; Dewi Amanatun Suryani (NATAPRAJA, 2020)
HIV and AIDS cases in Yogyakarta city until March 2017 experience case addition. Increased cases of HIV AIDS can be caused due to the transmission of cases, also caused by increased awareness to check themselves. This issue is become responsibility together so that the effort in treatment need collaboration. The purpose of this study was to determine Collaborative Governance in HIV AIDS Prevention in Yogyakarta City and to find out how far Collaborative Governance contributes to tackling HIV AIDS in Yogyakarta City. This study uses a qualitative descriptive approach with data collection techniques carried out through participant observation, in-depth interviews, and documentation studies. The results showed that Collaborative Governance in the prevention of HIV and AIDS in the city of Yogyakarta had been carried out quite well, the implementation of collaboration was not binding and there was no hierarchical structure. The collaboration takes place in accordance with the work program and duties and functions of each institution. Motivation together there is a shared belief in carrying out collaboration, but the mutual understanding is not optimal because of the implementation of separate collaborations. Capacity aspects of financial resources, facilities and human resources are still limited. The impact of Collaborative governance in overcoming HIV and AIDS is to be able to minimize the spread of HIV and AIDS in the city of Yogyakarta as well as an increase in the handling of people affected by HIV and AIDS.